Microglial Immunometabolism in Alzheimer’s Disease - Shippy, Daniel C.; Ulland, Tyler K. (Frontiers in Cellular Neuroscience, 2020)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by amyloid-β (Aβ) plaques and the formation of neurofibrillary tangles (NFTs) composed of hyperphosphorylated tau. In response to Aβ and tau aggregates, microglia, the primary innate immune cells of the central nervous system (CNS), facilitate Aβ and tau clearance and contribute to neuroinflammation that damages neurons. Microglia also perform a wide range of other functions, e.g. synaptic pruning, within the CNS that require a large amount of energy. Glucose appears to be the primary energy source, but microglia can utilize several other substrates for energy production including other sugars and ketone bodies. Recent studies have demonstrated that changes in the metabolic profiles of immune cells, including macrophages, are important in controlling their activation and effector functions. Additional studies have focused on the role of metabolism in neuron and astrocyte function while until recently microglia metabolism has been considerably less well understood. Considering many neurological disorders, such as neurodegeneration associated with AD, are associated with chronic inflammation and alterations in brain energy metabolism, it is hypothesized that microglial metabolism plays a significant role in the inflammatory responses of microglia during neurodegeneration. Here, we review the role of microglial immunometabolism in AD.